2021
DOI: 10.1186/s13018-021-02371-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a second-generation appropriateness classification system for total knee arthroplasty: a prospective cohort study

Abstract: Background To test the validity of a second-generation appropriateness system in a cohort of patients undergoing total knee arthroplasty (TKA). Methods We applied the RAND/UCLA Appropriateness Method to derive our second-generation system and conducted a prospective study of patients diagnosed with knee osteoarthritis in eight public hospitals in Spain. Main outcome questionnaires were the Western Ontario and McMaster Universities Osteoarthritis In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…There is strong consensus that TKA should be offered to individuals with knee symptoms that are negatively affecting quality of life despite a trial of non-surgical therapies. 15 16 25–27 However, only 71% of our TKA recipients had received recommended OA therapies. Although we did not find that receipt of prior recommended OA therapies was associated with TKA outcome, it is reasonable to expect that non-surgical therapies have been exhausted before a costly and potentially risky procedure is performed.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…There is strong consensus that TKA should be offered to individuals with knee symptoms that are negatively affecting quality of life despite a trial of non-surgical therapies. 15 16 25–27 However, only 71% of our TKA recipients had received recommended OA therapies. Although we did not find that receipt of prior recommended OA therapies was associated with TKA outcome, it is reasonable to expect that non-surgical therapies have been exhausted before a costly and potentially risky procedure is performed.…”
Section: Discussionmentioning
confidence: 96%
“… 15 16 18 Using the Spanish criteria, Escobar et al found that appropriate candidates were more likely than those deemed inappropriate to experience minimally important improvements in pain and function at follow-up, but outcomes were similar for those deemed appropriate versus uncertain and level of satisfaction was similar across groups. 15 Furthermore, both the Spanish and AAOS criteria ask surgeons to make assumptions regarding the patients whose TKA appropriateness they are assessing. In development of the Spanish criteria, experts were instructed to assume that the patient had unilateral knee symptoms, a BMI<40 kg/m 2 , adequate social support and received appropriate knee OA management and their expectations had been addressed appropriately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Short-term outcomes were as follows: operation time, length of hospital stay, and straight leg raising time. Long-term clinical effect mainly including Insall-Salvati ratio; range of motion at 1 month, 3 months, and 1 year following TKR; and visual analog scale (VAS) at 1 month, 3 months, and Knee Society Score (KSS) score [ 12 , 13 ] at 1 year following TKR. The ISR Insall-Salvati ratio is the ratio between the length of the patellar tendon and length of the patella.…”
Section: Methods and Analysismentioning
confidence: 99%